Editorial: antigenic response to CT‐P13 and infliximab originator in IBD shows similar epitope recognition—evidence from basic science supports safe switching to biosimilars. Authors' reply. Issue 5 (9th August 2018) - Goncalves, J.; Magro, F.; Danese, S.; Lakatos, P. L.; Ben‐Horin, S.
Abstract : Linked Content This article is linked to Goncalves et al and Pouillon et al papers. To view these articles visithttps://doi.org/10.1111/apt.14808 andhttps://doi.org/10.1111/apt.14847 .